Uma análise do Programa Nacional de Fortalecimento da Agricultura Familiar (PRONAF) em Campina Grande - PB - Araújo, Maria Eduarda Dias de (2018)
Within this dissertation we seek to build a field of understanding by articulating family agriculture with public policies of rural development. It is also proposed to analyze whether PRONAF, as a public policy, has promoted rural development in a specific reality: the municipality of Campina Grande-PB. For this, it is intended to map rural communities and agricultural activities developed in Campina Grande in order to know the rural of the municipality; identify the credit lines provided to the family farmers by the program so as to reveal which are the most accessed by them; to ascertain the applicability of financing of production, training and technical follow-up, and to verify if there was an increase in production and income generation after access to credit. In the meantime, a secondary database (books, articles, dissertations) and documents were made available by the Special Secretariat for Agriculture and Agrarian Development (SEAD), the Brazilian Institute of Geography and Statistics (IBGE) and the Matrix data from the Rural Credit of the Central Bank of Brazil. The research is qualitative, descriptive and analytical. The primary data collection was carried out, primarily, through semi-structured individual interviews, with an open itinerary, directed to family farmers and other social actors involved with the Program. The systematized results indicate that most of the beneficiaries fall into group B, representing the greater demand for rural credit in terms of the volume of resources and the number of proposals contracted and accessing mostly the Rural Microcredit line. It was also observed that some farmers resist the renewal of the contract, based on the rural debts that contracted and the lack of information in the hiring of PRONAF. It is also identified with this research the predominance of financing livestock activities to the detriment of the financing of agricultural activities in the municipality. In addition to the water problem faced by farmers, it is confirmed that insufficient technical assistance, bureaucratic impediments and the ability to supervise through financial agents are the most marked difficulties for the effectiveness of the program. Thus, the research revealed that PRONAF, even in the face of the availability of credit for the financing of agricultural activities, presents failures in its execution in the municipality. Finally, the objective of analyzing the PRONAF in relation to the development of the rural municipality studied, highlighted the potentialities and difficulties to be overcome by this public policy in rural areas. Therefore, it is indispensable to promote discussions on this subject, observing the obstacles of this public policy in fomenting transformations in the rural world.